PEMODELAN DAN ANALISA STRUKTUR MEKANIKA PADA KONTROL SISTEM ADAPTIF END EFFECTOR DENGAN DYNAMIXEL AX-18A MOTOR SERVO - Lydia Anggraini; Ardhi Bebi Laksono (Journal of Mechanical Engineering and Mechatronics, 2018)
The main objective of this project is to make a descriptive contribution to the understanding of adaptive end-effector design combined with servo motors. The simulation and design of this tool is located at the end of the robotic arm, which is one of the most researched topics in the world of robotics and the automation industry. End-effector is a design system in an automation process that must take into account the many possibilities of statics and mechanical responses in the development of facing intense competition in the industrial world. To determine the enhancements on a robot, the end-effector will be designed taking into account the various possibilities that occur in various variations on the workpiece response, so that it can simulate various levels of friction and pressure as well as the effects of end-effector contacts with various objects. This thesis introduces an integrated design process for the design of two-finger Gripper using simulation. To facilitate the integrated design of the Gripper, the author uses Matlab R2015a software/ Simulink (SimMechanics) and Inventor as a 3D Cad Model. The Servo motor that will be used here is a type of Dynamixel AX-18A servo motor which has a speed of 97RPM and Torque of 1.8 N.m with a 12Volt voltage. To deal with the industrial revolution 4.0, design and design such as this tool will help in the process of improvisation as technology is growing rapidly in the hope of minimizing excessive costs when making improvements. From this thesis can be seen the power response, torque, speed, power in, power out, efficiency and current. When a case requires certain specifications, then with this calculation it can easily solve the problem simply by replacing the motors that are in accordance with the desired specifications.